Deadly discrimination: Implications of “Missing Girls” for workplace safety - Tan, Zhibo; Wei, Shang-Jin; Zhang, Xiaobo (Elsevier, 2021)
We examine an indirect but potentially deadly consequence of the “missing girls” phenomenon. A shortage of brides causes many parents with sons of marriageable age to work harder and seek higher-paying but dangerous jobs. In response, employers invest less in workplace safety, which in turn increases work-related mortality. Drawing from a broad range of data sets and taking advantage of large regional and temporal variations in sex ratios in China, we demonstrate that in areas with more severe shortages of young women, the cohort of parents with sons of marriageable age suffers a higher incidence of accidental injuries and workplace deaths.